1995
DOI: 10.1111/j.1398-9995.1995.tb01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of allergen provocation on inflammatory cell profile and endothelin‐like immunoreactivity in guinea‐pig airways

Abstract: The effect of allergen challenge on the number of leucocytes and the concentration of endothelin 1-like immunoreactivity (ET-LI) in bronchoalveolar lavage fluid (BALF) was investigated in guinea-pigs sensitized to Ascaris suum. The animals were twice exposed to allergen aerosol. All animals responded to the second challenge with bronchoconstriction. Twelve hours later, a significant increase in the number of eosinophilic granulocytes in BALF, compared to unsensitized and unprovoked control animals, was noted. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…In agreement with this, we have also recently detected increased levels of ET-l-LI in BALF from guinea pigs that developed bronchoconstriction after allergen challenge but not in animals where bronchoconstriction was induced by carbachol [19].…”
Section: Discussionsupporting
confidence: 70%
“…In agreement with this, we have also recently detected increased levels of ET-l-LI in BALF from guinea pigs that developed bronchoconstriction after allergen challenge but not in animals where bronchoconstriction was induced by carbachol [19].…”
Section: Discussionsupporting
confidence: 70%
“…When compared with control mice treated with rat IgG (4.4 ± 0.8 x 105 eosinophils/ml), antigen-induced eosinophilia was slightly inhibited by 25 µg of anti-ET antibody (2.5 ± 0.4 X 105 eosinophils/ml) and markedly inhibited with 50 pg of antibody (1.3 ± 0.3 x 105 eosinophils/ml) ( Figure 3). It has previously been reported that ET-like immunoreactivity was increased after allergen provocation is sensitized guineapig airways (19). Taken together, these observations suggest the involvement of endogenous ET in the development of lung granulocyte infiltration after allergen provocation.…”
Section: Resultsmentioning
confidence: 53%
“…These methods are commonly employed and are fully described elsewhere. 32,33 Percent inhibition of inflammatory cell infiltration into the airways was calculated according to the following equation:…”
Section: Aerodynamic Characterizationmentioning
confidence: 99%